Faktor-Faktor yag Berhubungan dengan Perawatan Payudara pada Ibu Nifas - Bettywati, Bettywati; Yellyanda, Yellyanda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze factors related to breast care for postpartum mothers at H. Abdul Manap Hospital, Jambi City. The research method used is quantitative research with a cross-sectional design. The research results showed that most respondents, 84.4%, carried out breast care for postpartum mothers. The chi-square test analysis results showed a significant relationship between education and breast care in postpartum mothers with a p-value = 0.036, and there was a meaningful relationship between knowledge and breast care in postpartum women with a p-value = 0.000. Chi-square test analysis results. The results showed no significant relationship between parity and breast care in postpartum mothers with p-value = 1.000, and there was a meaningful relationship between motivation and breast care in postpartum women with p-value = 0.000. In conclusion, breast care for postpartum mothers is related to the mother's education, knowledge, and motivation. Keywords: Postpartum Mothers, Knowledge, Breast Care